MnO Stabilized in Carbon‐Veiled Multivariate Manganese Oxides as High‐Performance Cathode Material for Aqueous Zn‐Ion Batteries. Issue 4 (23rd December 2020) - Jiang, Wanwei; Shi, Haiting; Xu, Xijun; Shen, Jiadong; Xu, Zhiwei; Hu, Renzong
Abstract : Aqueous Zn‐ion battery has emerged as one of the most prospective energy storage devices due to its low cost, high safety, and eco‐friendliness. However, Zn‐ion batteries are bottlenecked by significant capacity fading during long‐term cycling and poor performance at high current rates. Here, we report an available cooperation of multivariate manganese oxides@carbon hybrids (MnO2 /MnO@C and MnO2 /Mn3 O4 @C) via a plasma‐assisted design as an attractive Zn‐ion cathode. Among them, the MnO2 /MnO@C cathode exhibits a reversible specific capacity of 165 mAh g −1 over 200 cycles at a high rate of 0.5 A g −1, and possesses great rate performance with high capacities of 110 and 100 mAh g −1 at a high rate of 0.8 and 1 A g −1, respectively. The good cathode performance significantly results from the facile charge transfer and ions (Zn 2+ and H + ) insertion in the manganese oxides/carbon hybrids featuring phase stability behavior in the available cooperation of multivalence and carbon conductive substrates. This work will promote the Zn‐manganese dioxide system for the design of low‐cost and high‐performance aqueous rechargeable Zn‐ion batteries. Abstract : The MnO2 /MnO@C hybrid has good structural stability due to the available cooperation of Mn (II) and Mn (IV) phases during the Zn 2+ / H + insertion into the manganese oxides, which accelerates ion/electron migration rates and improves the cycle performance.